Non-invasive prenatal testing in Germany: a unique ethical and policy landscape - Bowman-Smart, H; Wiesemann, C; Horn, R (Springer Nature, 2022)
Non-invasive prenatal testing (NIPT) has been available commercially in Europe since approximately 2012. Currently, many countries are in the process of integrating NIPT into their publicly funded healthcare systems to screen for chromosomal aneuploidies such as trisomy 21 (Down syndrome), with a variety of implementation models. In 2019, the German Federal Joint Committee (G-BA), which plays a significant role in overseeing healthcare decisions in Germany, recommended that NIPT be reimbursed through public insurance. Following this recommendation, NIPT will be offered on a case-by-case basis, when a pregnant woman, after being counselled, makes an informed decision that the test is necessary in her personal situation. This model differs significantly from many other European countries, where NIPT is being implemented either as a first-tier screening offer available for all pregnancies, or a contingent screen for those with a high probability of foetal aneuploidy (with varying probability cut-offs). In this paper we examine how this unique approach to implementing NIPT in Germany is produced by an ethical and policy landscape resulting from a distinctive cultural and historical context with a significant influence on healthcare decision-making. Due in part to the specific legal and regulatory environment, as well as strong objections from various stakeholders, Germany did not implement NIPT as a first-tier screen. However, as Germany does not currently publicly fund as standard other forms of prenatal aneuploidy screening (such as combined first trimester screening), neither can it be implemented as a screen contingent on specific probability cut-offs. We discuss how German policy reflects the echoes of the past shaping approaches to new biotechnologies, and the implications of this unique model for implementing NIPT in a public healthcare system.